Coffee Shop VS Library: Concept of Learning Spaces for New Library Users - Aliwijaya, Araf; Syahfitri, Dwi Retno (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2023)
ABSTRACT Coffee Shops have been increasingly mushrooming due to the trend of coffee culture in Indonesia, not to mention the occurrence in Yogyakarta City. The habit of going to the Coffee Shop is not only to taste typical coffee, but to just hang out, relax, discuss, or obtain information outside the library. This study aims to find out the perspective of users about the attraction of visiting the Coffee Shop or library. This study also answers the question of what impact can be caused by the existence of a café in the library. Method. This study used qualitative methods with observation and interview data collection techniques. Data was collected by interviewing 17 Coffee Shop and library visitors. Analysis. Data is collected and analyzed descriptively and systematically. Results. Users are more interested in visiting the Coffee Shop for the learning process than the library. Users look for information at the Coffee Shop because of the longer opening time, more relaxed environment, access to eat and drink, open discussion rooms, internet access, and facilities available are more supportive than the library. Coffee Shop VS Perpustakaan: Konsep Tempat Belajar Pemustaka Generasi Baru ABSTRAK Coffee Shop sudah semakin berkembang kian menjamur akibat adanya tren budaya ngopi di Indonesia, tidak terlepas pula terjadi di Kota Yogyakarta. Kebiasaan pergi ke Coffee Shop tidak hanya untuk mencicipi kopi khas, melainkan untuk sekedar nongkrong, bersantai, diskusi, atau memperoleh informasi di luar perpustakaan. Tujuan penelitian ini untuk untuk mengetahui perspektif pemustaka tentang daya tarik untuk mengunjungi Coffee Shop atau perpustakaan. Penelitian ini juga menjawab pertanyaan mengenai asumsi apakah dampak yang dapat ditimbulkan dengan adanya café di perpustakaan. Metode. Penelitian ini menggunakan metode kualitatif dengan teknik pengambilan data observasi dan wawancara. Data dikumpulkan dengan melakukan wawancara 17 pengunjung Coffee Shop dan perpustakaan. Analisis. Data dikumpulkan dan dianalisis secara deskriptif dan sistematis. Hasil. Pemustaka lebih tertarik mengunjungi Coffee Shop untuk proses pembelajaran daripada perpustakaan. Pemustaka mencari informasi di Coffee Shop karena waktu buka yang lebih lama, lingkungan yang lebih santai, akses makan dan minum, ruang diskusi terbuka, akses internet dan fasilitas yang tersedia lebih mendukung daripada perpustakaan.